Biomechanical evaluation of partial prosthesis on implants with different platforms in the posterior region of mandible: in silicon analysis - Reis, Francisco Carlos dos Santos (2022)
This study evaluated the behavior of implants with different cervical geometries in a three-element prosthesis in the posterior region of the mandible using the finite element method. For this, four models were created in SolidWorks Professional 2013® software, in the format of a bone block, simulating the rehabilitation of three elements in zirconia-based ceramic, supported by two implants in the regions of elements 44 and 46. The variables were diferent cervical geometries (bone level – NO – or gingival level – NG) Arranged: M1 – two NO implants; M2 – two NG implants; M3 – implant of element 44 in NO and element 46 in NG, and; M4 – implant element 44 in NG and element 46 in NO. The models were exported to Ansys Workbench 14.0® software. For occlusal loading, 300 N on the first molar and 150 N on the premolars. The M4 model presented lower compressive stress in cortical bone (49.55 MPa), while for medullary bone; the M2 model presented lower compressive stress (3.89 MPa). In implants in the premolar and molar region, models M3 and M1 showed lower von Mises stress peaks, with 67.78 MPa and 97.91 MPa, respectively. The M4 model showed the lowest von Mises stresses for the abutment in the premolar region (66.61 MPa), while the M3 model showed the lowest abutment stress in the molar region (113.63 MPa). It was concluded that there is an influence of the cervical geometry of the implants on the stress distribution and that NO implants had higher stress peaks than NG implants.